2023
DOI: 10.3390/biology12050669
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Durability of a Quaternary Ammonium Compounds-Based Surface Coating to Reduce Surface Contamination

Abstract: Foodborne diseases are of major concern as they have a significant impact on public health, both socially and economically. The occurrence of cross-contamination of food in household kitchens is a serious threat and the adoption of safe food practices is of paramount importance. This work aimed to study the effectiveness and durability of a commercial quaternary ammonium compound-based surface coating which, according to the manufacturer, retains its antimicrobial activity for 30 days, and is suitable for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Regarding quaternary ammonium-based components, it is important to note that not all materials containing these compounds maintain their antibacterial effectiveness over an extended period . The persistence of this effect largely depends on the ability of the antibacterial monomer to cross-polymerize effectively within the dental material .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding quaternary ammonium-based components, it is important to note that not all materials containing these compounds maintain their antibacterial effectiveness over an extended period . The persistence of this effect largely depends on the ability of the antibacterial monomer to cross-polymerize effectively within the dental material .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding quaternary ammonium-based components, it is important to note that not all materials containing these compounds maintain their antibacterial effectiveness over an extended period. 61 The persistence of this effect largely depends on the ability of the antibacterial monomer to cross-polymerize effectively within the dental material. 35 In the case of the SiQuac-silanized particles used in our study, the chemical bonding of SiQuac to the shell likely contributes to the retention of the antibacterial properties even after aging.…”
Section: Dental Adhesives' Mechanical and Bondingmentioning
confidence: 99%
“…Most authors report that ISO 22196 [11], without modifications, fails to accurately simulate real environmental and usage conditions and allows for inflated values or erroneous claims of antimicrobial activity, thus compromising the validity of the efficacy result [17,29,37,68]. Since the parameters required by the standard are the optimum conditions to ensure the efficacy of the antibacterial activity of the surfaces, they will not produce the same efficacy results when applied in real-life environments such as hospitals, the food industry and household use, making this protocol a fictitious claim of antibacterial efficacy by the product.…”
Section: Factors Affecting the Validity Of The Antimicrobial Test Met...mentioning
confidence: 99%
“…These authors provided no comments on whether this change in densities significantly affected the antibacterial activity efficacy of the compounds tested. Conversely, 37% of the authors (20 studies) [2,8,24,27,31,32,[38][39][40][41]46,47,50,52,54,56,59,66,68] reported an adjustment of the bacterial inoculum volume due to the size of the test specimen used. This modification has not been reported to influence the result of the protocol since ISO 22196 allows for different sizes/measurements of the test specimen and plastic cover film, as long as the inoculum volume is adjusted to be proportional to the area of the cover film used.…”
Section: Inoculummentioning
confidence: 99%
See 1 more Smart Citation